Microscopic colitis: a population‐based case series over a 9‐year period in Northern Ireland. (7th June 2018) - Moore, M.; Coleman, H. G.; Allen, P. B.; Loughrey, M. B.
Abstract: Aim: We report clinicopathological experience of microscopic colitis (MC) in a population‐based case series in Northern Ireland over a 9‐year period. Method: The pathology laboratory information system within a large teaching centre serving two healthcare trusts was interrogated for cases coded between 2008 and 2016 as collagenous colitis (CC) or lymphocytic colitis (LC). Demographic, clinical and follow‐up information was collected from healthcare records. Results: A total of 326 new diagnoses of MC were identified, an average annual incidence of 6.7 per 100 000 population. The average annual incidence of CC and LC was 5.0 and 1.7 per 100 000 population, respectively. For coding reasons it is likely that LC data are incomplete. Of 191 cases diagnosed by specialist gastrointestinal pathologists, 141 patients had CC and 50 patients had LC. Both CC and LC predominantly involved women aged 60–79. Some 15% demonstrated endoscopic abnormalities. Endoscopic sampling protocols varied widely: 30% of individuals with CC and 32% of those with LC had the right and left colon sampled separately, with histology concordant in 95% of cases. Of the 191 cases, only one case (of LC) was refractory to treatment; the rest exhibited a clinical response. Only 35 patients had follow‐up endoscopy and biopsies, and three of each diagnosis showed persistent disease on histology. Conclusion: Overall, CC and LC are benign conditions with similar demographics, clinical associations, management and outcomes. Separate sampling of the right and left colon is advised at colonoscopy if this diagnosis is being considered, but left colonic sampling, which can be performed at flexible sigmoidoscopy, will diagnose the vast majority of cases.